Genetic Diversity of Drought Tolerant Upland Rice (Oryza sativa L.) Genotypes (The Agriculturists, 2016)
Genetic divergence of thirty three drought tolerant rice (Oryza sativa L.) genotypes were studied through Mohalanobiss D2 and principal component analysis for twelve characters. The genotypes were grouped into seven clusters. The cluster I and II were comprised of the maximum number of genotypes (eight) in each followed by cluster V containing five genotypes. The highest inter-cluster distance was in between cluster III and I (368.64) indicating a wide genetic diversity between these two clusters followed by clusters VII and III (346.04). The lowest inter-cluster distance was in between cluster IV and II (42.46) followed by cluster VI and IV (63.29) indicating that the genotypes of these clusters were genetically close. The intra cluster distance in the entire seven clusters was less, which indicate that the genotypes within the same clusters were closely related. Considering the magnitude of genetic distance, contribution of different characters towards the total divergence and magnitude of cluster means for different characters performance, BR 7391-2B-7, BR 7392-2B-25, BR 6855-2B-11-3-4, BR 6855-2B-11-3-5  from cluster I, genotypes BR 6976-2B-15, and Morichbati from cluster III, genotypes BR 7187-2B-2-5 from cluster IV, genotype BR 7187-2B-2-3 and BR 7181-2B-35-2 from cluster V and genotypes BR 6855-2B-11-3-7 and BRRI dhan 42 from the cluster VII are likely to perform better if used in hybridization program.The Agriculturists 2015; 13(2) 133-139